Plant Root Exudates Are Involved in Bacillus cereus AR156 Mediated Biocontrol Against Ralstonia solanacearum - Wang, Ning; Wang, Luyao; Zhu, Kai; Hou, Sensen; Chen, Lin; Mi, Dandan; Gui, Ying; Qi, Yijun; Jiang, Chunhao; Guo, Jian-Hua (Frontiers in Microbiology, 2019)
The biological control process mediated by microbes relies on multiple interactions among plants, pathogens and biocontrol agents (BCAs). One such efficient BCA is Bacillus cereus AR156, a bacterial strain that controls a broad spectrum of plant diseases and potentially works as a microbe elicitor of plant immune reactions. It remains unclear, however, whether the interaction between plants and B. cereus AR156 may facilitate composition changes of plant root exudates and whether these changes directly affect the growth of both plant pathogens and B. cereus AR156 itself. Here, we addressed these questions by analyzing the influences of root exudate changes mediated by B. cereus AR156 during biocontrol against tomato bacterial wilt caused by Ralstonia solanacearum. Indeed, some upregulated metabolites in tomato root exudates induced by B. cereus AR156 (REB), such as lactic acid and hexanoic acid, induced the growth and motile ability of in vitro B. cereus AR156 cells. Exogenously applying hexanoic acid and lactic acid to tomato plants showed positive biocontrol efficacy (46.6% and 39.36%) against tomato bacterial wilt, compared with 51.02% by B. cereus AR156 itself. Furthermore, fructose, lactic acid, sucrose and threonine at specific concentrations stimulated the biofilm formation of B. cereus AR156 in Luria-Bertan- Glycerol- Magnesium medium (LBGM), and we also detected more colonized cells of B. cereus AR156 on the tomato root surface after adding these four compounds to the system. These observations suggest that the ability of B. cereus AR156 to induce some specific components in plant root exudates was probably involved in further biocontrol processes.